The acceptance towards Sunnah food among Malaysian community / Nur Akmal Bahiah Badrul Hisham, Abdul Rauf Ridzuan and Aini Faezah Ramlan - Badrul Hisham, Nur Akmal Bahiah; Ridzuan, Abdul Rauf; Ramlan, Aini Faezah (Faculty of Communication & Media Studies, 2019)
The research examined the study of Theory of Planned Behaviour and perceptions towards the Sunnah food among Malaysian community. The minimum amount of survey within sample size was determined through Raosoft Calculator software by using purposive sampling method. Descriptive quantitative research was conducted through survey using questionnaire form from Google Docs, involving 300 respondents from Malaysia. The collected data were analysed by using SPSS version 20. The independent variable, which is Theory of Planned Behaviour involved 4 elements which is (1) Attitude, (2) Subjective Norms, (3) Perceived Behavioural Control (PBC) and (4) Knowledge. While the dependent variable studied of the Malaysian community acceptance towards Sunnah food. The suitable research theory implemented throughout the study is Theory of Planned Behaviour, which is chosen to observe the relationship among the components of TPB with the behaviour of consumer by taking into consideration the Sunnah advantages. Theory of planned behaviour were collected from various social media literatures that included both books and article journals (Rozilah Hamdan, 2013). The hypothesis testing gained by using Multiple Linear regression shows that there are two different reading which formed different results. The first results is based on Beta value which shows the most significant relationship between the independent towards the dependent variables. Thus the result indicated Knowledge (β = 0.422) is the strongest relationship towards dependent variables (acceptance). However, based on significant value in Coefficient Multiple Linear Regressions Analysis, the null hypothesis of Attitude (0.000), Subjective Norms (0.001), Perceived Behavioural Control (0.289) and Knowledge (0.000) is being accepted with significant value below than p=0.10. While when R-value indicates multiple R, which is the correlation of all the independent variables against dependent variable, which is 0.898.and the R2 which is 0.806 explain the amount of variance in the dependent variables by all the dependent variable.